Sistem Pemberdayaan Masyarakat Melalui Program Digitalisasi UMKM Desa Srimukti - Yayan Hendayana; Annisa Azahra Aulia; Doni Ferdinan Irawan; Dyah Pratiwi; Kefas Kristian Telaumbanua; Nadia Putri Iskandar; Nawang Dwi Anjani; Fitriani Thalitha; Rizky Maulana; Septiana Cahyaningrum T.P; Shabina Deanova (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2023)
Community empowerment is a concept of economic development that encapsulates community values ​​to build a new paradigm in development that is people-centered, participatory. Within this framework efforts to empower communities (empowering) can be studied from 3 (three) aspects: First, ENABLING, namely creating atmosphere that allows the potential of society to develop. Second, EMPOWERING, namely strengthening the potential of the community through concrete steps involving the provision of various inputs and opening up various opportunities that will make the community more empowered. Third, PROTECTING, namely protecting and defending the interests of the weak. Micro, Small and Medium Enterprises or MSMEs are small-scale businesses that involve a limited number of employees and capital. Generally, they operate in various sectors, from trading to manufacturing. MSMEs have several strengths, one of which is the ability to quickly and flexibly respond to local needs. They often provide products or services that suit local preferences. The digitization of MSMEs is the change of conventional business transactions to online. The development of technology and information can be said to have influenced various aspects, including business. The UMKM Digitalization Program includes e-Farming by utilizing digital technology in agriculture to increase production capacity and cost efficiency. e-Commerce includes strengthening capacity in digital marketing and marketing MSMEs to global markets through digital platforms.